Transforming Consumer Behavior Through Cloud Kitchen and Digitalization Boosting MSMES Sustainability in The F&B - Telaumbanua, Bernadeth Bekania; Wiriasubranta, Farhan; Wulandari, Karina Tri Cahya; Husniah, Nuraini Farah; Khairana, Imannia; Nuraisyah, Ani (Business Review and Case Studies, 2023)
Cloud kitchen is a system that allow business owner to serve customers without facilitate a dining-in establishments. The idea of cloud kitchen has proof its usefulness due to COVID-19 pandemic, where many food and beverage (F&B) sector owners especially the medium, small, and micro enterprises (MSMES) suffer because they could not provide their service due to government-imposed measures to limit the movement of people and activities in an effort to control the spread of COVID-19. This research aims to explore the concept of cloud kitchen further, as well as examining the relation between the rapid development of technology has allow many F&B sector owner to survive during and post pandemic. This research employed a systematic literature review with a qualitative approach. A total of 329 studies were identified and 12 are selected and included in the review. These 12 journals were selected based on their relevance to the research topic, the quality and impact factor of the journal, the reputation of the authors who publish in the journal, and the rigor of the peer review process. The results indicate that cloud kitchen is a promising business model for F&B sector, it has maintain the sustainibility during pandemic and still keep it relevancy after pandemic. Several start-ups such as Gojek and Grab provide a food delivery service that allow partnership with MSME business owner, contributing in their effectiveness and efficiencies. Keywords: consumer behavior, MSMES, food and beverages, cloud kitchen